Seguimiento a la dinámica de los movimientos de remoción en masa con el uso de Sistemas Aéreos Remotamente Pilotados en el municipio de Cáqueza, Cundinamarca - Gutierrez Pacheco, Daniel Santiago (Universidad Antonio Nariño, 2021)
Mass removal movements are a very frequent environmental problem in the town of Cáqueza, Cundinamarca, which on many occasions has prevented the passage from the central zone to the eastern zone of the country. That is why three mass removal movements are analyzed with aerial images (drones) in the township during the months of February, March, and April 2021, which was developed through a survey to identify the characteristics of the terrain with the presence of movement and subsequently monitor the generation of collapsed scarps, the evolution of the topographic profile and volumetric change. Two areas are identified as having unstable areas and areas of material concentration that may soon collapse